2004
DOI: 10.1177/1077559503261262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of U.S. Army and Civilian Substantiated Reports of Child Maltreatment

Abstract: Little is known about the similarities and differences between civilian and military child maltreatment cases and no recent study has compared them directly. Understanding the nature of the problems in each could lead to identifying strengths and weaknesses for the development of more helpful prevention and treatment programs. The overall rates of child maltreatment in the U.S. civilian population (14.7 to 11.8 per 1,000) were about double the Army rates (7.6 to 6.0 per 1,000) from 1995 to 1999. These differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Raiha and Soma ( 1997 ) found rates of CM in the US Army to be 7.4 cases per 1000 children compared with 14 cases per 1000 in the civilian population. Rates obtained by McCarroll et al ( 2004 ) were similar. Rates of neglect follow this same pattern, with the US Army rates being approximately half the civilian rates.…”
Section: Prevalence Of Child Maltreatmentsupporting
confidence: 58%
See 2 more Smart Citations
“…Raiha and Soma ( 1997 ) found rates of CM in the US Army to be 7.4 cases per 1000 children compared with 14 cases per 1000 in the civilian population. Rates obtained by McCarroll et al ( 2004 ) were similar. Rates of neglect follow this same pattern, with the US Army rates being approximately half the civilian rates.…”
Section: Prevalence Of Child Maltreatmentsupporting
confidence: 58%
“…That said, most studies that use population level rates of offi cially reported CM fi nd that military families have lower overall rates of CM (McCarroll, Ursano, Fan, & Newby, 2004 ;Raiha & Soma, 1997 ; than civilian families. Raiha and Soma ( 1997 ) found rates of CM in the US Army to be 7.4 cases per 1000 children compared with 14 cases per 1000 in the civilian population.…”
Section: Prevalence Of Child Maltreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative hypothesis is that child abuse and neglect are less serious in the army than in the civilian sector of US society and that children are, in fact, not the victims of multiple maltreatments. In a previous paper, we found that differences in the army and the US were largely due to the high rates of neglect found in the US civilian sector (McCarroll et al, 2004b) and more physical abuse was classified as severe in the army (McCarroll et al, 2004a).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, active duty soldiers had higher levels of severe spousal aggression than comparable civilian populations (Heyman & Neidig, 1999). By contrast, evidence suggests that rates of child maltreatment are lower within military families than civilian ones (McCarroll, Ursano, Fan, & Newby, 2004;Raiha & Soma, 1997), due to relatively low rates of child neglect among military families. The presence of both substance abuse and family violence in military populations suggests that the cooccurrence of these issues might be of concern to clinicians.…”
mentioning
confidence: 89%